Performance investigation of two-level reduced-switch D-STATCOM in grid-tied solar-PV array with stepped P&O MPPT algorithm and modified SRF strategy - Meenakshi Rastogi; Aijaz Ahmad; Abdul Hamid Bhat (Journal of King Saud University: Engineering Sciences)
In this paper, a Two-Level, Three-Phase, Reduced-Switch (2L3PRS) Voltage Source Converter (VSC) based Distribution Static Synchronous Compensator (DSTATCOM) integrated with a grid-tied solar photo-voltaic (PV) array has been discussed, and its performance investigation has been carried out. A versatile control strategy is proposed, which gives the system maximum power point tracking capability with a stepped perturbation and observation (P&O) algorithm and the grid current is maintained at unity power factor. The layout, in addition to the control technique, helps in supplying active power to the power grid and feeding active and reactive power demand of the 3-phase reactive unbalanced load. Modified Synchronous Reference Frame (MSRF) theory-based current control methodology is implemented to sustain DC-link voltage and to maintain the voltage balancing across split capacitors under all loading conditions. This modified algorithm generates switching pulses for three-phase VSI with only four IGBT switches for fulfilling the desired objectives like maintaining a constant DC link voltage, balancing split-capacitor voltages, balancing the power-sharing between the power grid and the solar-PV energy system, balancing the grid currents and voltages in case of unbalanced loading conditions and maintaining unity power factor operation of the grid by making the D-STATCOM compensate for load reactive power. The proposed system is replicated in MATLAB/Simulink using SimPowerSystems software-based environment. The experimental outcomes have been obtained with a digital real-time simulator to vindicate the simulation results. The experimental, as well as simulation results of the proposed real-time-based model, are demonstrated for three unbalanced single-phase inductive linear loads and with a load on one Phase kept open in the Power Factor Correction (PFC)mode of operation of D-STATCOM.